Ephedra alata Seeds Confer Kidney Protection against Early Life Exposure to Acephate by Regulating Oxidative Insult and Activating Autophagy - Mufti, Afoua; Feriani, Anouar; Contreras, María del Mar; Nehdi, Saber; Hfaeidh, Najla; Tlili, Nizar; Harrath, Abdel Halim (Life (Basel, Switzerland), 2023)
The aim of the current work was to examine for the first time the nephropreventive capacity of Ephedra alata seed extract (E) against maternal exposure to acephate in rat offspring. The in vivo results revealed that E. alata supplementation for 28 days (40 mg/kg b.w.) significantly attenuated the nephrotoxicity in adult offspring induced by acephate. In fact, it decreased the levels of creatinine and uric acid and increased the albumin content compared to the intoxicated group. The in utero studies showed that E. alata inhibited the renal oxidative stress generated by acephate exposure by reducing lipid peroxidation and enhancing antioxidant biomarker activities (GSH, CAT, and SOD). The inhibition of DNA fragmentation and the improvement of the ultrastructural changes highlighted the prophylactic effect of E. alata in renal tissue. Additionally, the immunofluorescence study showed the upregulation of LC3 gene expression, suggesting the capacity of E. alata extract to stimulate autophagic processes as a protective mechanism. Molecular docking analysis indicated that hexadecasphinganine, the major compound in E. alata, has a higher affinity toward the Na+/K+-ATPase, epithelial sodium channel (ENaC), and sodium hydrogen exchanger 3 (NHE3) genes than acephate. Hexadecasphinganine could be considered a potential inhibitor of the activity of these genes and therefore exerted its preventive capacity. The obtained findings confirmed that E. alata seed extract exerted nephropreventive capacities, which could be related to its bioactive compounds, which possess antioxidant activities.